QUANTITATIVE ANALYSIS OF GEOMORPHIC RESPONSES AND TOPSIS APPROACHE ANALYSIS TO ACTIVE TECTONIC PROCESS: A CASE STUDY OF THE NORTHEAST OF THE AURES (TEBESSA) - Taib HASSAN; Hadji RIHEB (Analele Universităţii din Oradea: Seria Geografie, 2024)
This study combines GIS and remote sensing technologies to analyze geomorphological changes in the Tebessa basin, focusing on key indices such as hypsometric integral (HI) and stream sinuosity (SS). The objective was to assess how drainage anomalies and tectonic activity influence flow and relief patterns. Asymmetry and topographic factors were incorporated into a geographic information system, and the region was classified into four IRAT classes: high, medium, low, and rank. Results identified highly deformed areas near active tectonic anomalies, highlighting subsurface fault activity and its influence on river sinuosity. A new diagram illustrates the spatial evolution of these structures, providing insight into the region’s geological dynamics. The study also applied the TOPSIS method to prioritize watershed areas based on tectonic activity, offering a comprehensive analysis of the basin's geomorphological changes.